Clinical Characteristics and Inflammatory Immune Responses in COVID-19 Patients With Hypertension: A Retrospective Study - Chaoran Wu; Guangbo Qu; Lei Wang; Shiyu Cao; Dandan Xia; Baolong Wang; Xiaoyun Fan; Changhui Wang (Frontiers Media S.A., 2021)
Coronavirus disease (COVID-19) patients with cardiovascular and metabolic disorders have been found to have a high risk of developing severe conditions with high mortality, further affecting the prognosis of COVID-19. However, the effect of hypertension and angiotensin-converting enzyme inhibitors (ACEI) and angiotensin receptor blocker (ARB) agents on the clinical characteristics and inflammatory immune responses in COVID-19 patients is still undefined. In this study, 90 COVID-19 patients were divided into hypertension and nonhypertension groups. The hypertension group was divided into well-controlled and poorly controlled subgroups based on blood pressure levels; moreover, hypertensive patients were also divided into ACEI/ARB and non-ACEI/ARB subgroups according to the administration of ACEI/ARB antihypertensive agents. The clinical characteristics of and inflammatory immune biomarker levels in the different groups of COVID-19 patients were compared, and the association between the combined effect of hypertension with ACEI/ARB antihypertensive agents and the severity of COVID-19 was examined. The results showed that the levels of aminotransferase (AST) and hs-cTnI were higher in the hypertension group compared with the nonhypertension group. The long-term use of ACEI/ARB agents in patients had statistically significantly lower AST, low-density lipoprotein cholesterol (LDL-C), and oxygen uptake and lower white cell count, neutrophil count, and levels of CD4, CD8, CRP, and PCT but without statistical significance. In addition, compared with COVID-19 patients without hypertension, hypertensive patients without the use of ACEI/ARB had a higher risk of developing severity of COVID-19 (for poorly controlled patients: OR = 3.97, 95% CI = 1.03-15.30; for well-controlled patients: OR = 6.48, 95% CI = 1.77-23.81). Hypertension could cause organ damage in COVID-19 patients, but the long-term use of ACEI/ARB agents may be beneficial to alleviate this injury.